Die Reformdiskussion in der senegalesischen Sprachplanungspolitik - Diop, Ibrahima (Stellenbosch Papers in Linguistics Plus, 2012)
The reform discussion in Senegalese language planning indicates a review of the situation, which cannot be done without due attention to previous debates regarding the significance of African languages in the postcolonial culture and educational politics. Keywords: Schlüsselbegriffe: Bildungsreform, Sprachjakobinismus, Zentralismus, Pluralismus, Sprachkultur und Kultursprache education reform, language jacobinism, centralisation, pluralisation, language culture and language of culture